Correlation Between Storage Duration and Temperature of Uht Milk and The Growth of Streptococcus Sp. - Dea juni Safitri; Ikhsan Mujahid; Kurnia Ritma Dhanti; Arif Mulyono (Proceedings Series on Health & Medical Sciences, 2026)
Ultra-High Temperature (UHT) milk is processed by brief exposure to extremely high temperatures (approximately 135150C) to eliminate pathogenic microorganisms and extend shelf life. Streptococcus lactis, a member of the normal microflora in milk, contributes to fermentation processes; however, once the package is opened, the milk becomes susceptible to environmental contamination. Key factors influencing the growth of Streptococcus sp. in UHT milk include storage temperature, duration of storage, and nutrient availability. This study employed a time series design and was conducted in July 2025. Sixteen UHT milk samples were stored at 4C and 25C, with bacterial isolation performed on days 0, 1, 7, and 14. Data were analyzed using a repeated measures test. The results demonstrated a statistically significant correlation between storage duration and temperature and the growth of Streptococcus sp., with a p-value of 0.000 (p 0.05). These findings indicate that prolonged storage and higher temperatures are associated with increased bacterial proliferation.